2011
DOI: 10.1038/mt.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase Gene Transfer Restores Activity of Circulating Angiogenic Cells From Patients With Coronary Artery Disease

Abstract: Circulating angiogenic cells (CACs), represent a potential new therapeutic tool for the treatment of cardiovascular diseases, but their regenerative function is impaired in patients with coronary artery disease (CAD) and cardiac risk factors. The objective of this study is to assess the effect of lentiviral overexpression of endothelial nitric oxide synthase (eNOS) on the activity of CACs from patients with CAD and cardiac risk factors. In vitro and in vivo assays were employed to evaluate the regenerative cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 38 publications
2
43
0
1
Order By: Relevance
“…The idea of modifying stem cell-endothelial cells to improve therapeutic utility is not new [10], [35]. Thus, characterisation and modification of stem cell-endothelial cells at the level of TLR4 and other pattern recognition receptors represents a potentially important target for optimal and tailored cell therapy design.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of modifying stem cell-endothelial cells to improve therapeutic utility is not new [10], [35]. Thus, characterisation and modification of stem cell-endothelial cells at the level of TLR4 and other pattern recognition receptors represents a potentially important target for optimal and tailored cell therapy design.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin b 1 was chosen for use in the present study in an effort to facilitate homing of the ECFCs to the ischemic tissue, which would be expected to abundantly express ECM. Although ECFCs have been genetically modified in a number of earlier studies, most of those involved overexpression of angiogenic factors (e.g., vascular endothelial growth factor, hypoxia inducible factor-1a, hepatocyte growth factor, or endothelial nitric oxide synthase) in an effort to strengthen or accelerate the angiogenic function of ECFCs, not to facilitate homing [27][28][29][30][31][32]. Our approach might be unique in that context.…”
Section: Discussionmentioning
confidence: 99%
“…Witkowski et al showed that the number CD34 ϩ hematopoietic CACs decreased with 10 days of short-term reduced physical activity (rPA) in older, highly trained men, and that the change in CD34 ϩ /VEGFR2 ϩ cells in peripheral blood significantly predicted the change in the reactive hyperemic forearm blood flow response with reduced activity (57). NO has been shown to be necessary for proper cell migration and neovascularization in some CAC types (22,27,55) and is deficient in cardiometabolic disease states (12,58). CAC NO production can be influenced by activity and expression of endothelial nitric oxide synthase (eNOS), the enzyme that catalyzes the production of NO.…”
mentioning
confidence: 99%